Is There a Threshold for Medication Adherence? Lessons Learnt From Electronic Monitoring of Drug Adherence - Burnier, Michel (Frontiers in Pharmacology, 2019)
Medication adherence is a recognized problem in the management of patients with chronic diseases. While fighting against non-adherence, an important question frequently arises, i.e. how much adherence is enough to obtain the full treatment benefits? Most studies having attempted to answer this question have used large health care databases to quantify the percentage of days covered by the prescribed treatment and hence deduce a threshold below which benefits from therapy appear to be reduced. Here, the use of data obtained using electronic monitoring is discussed as another means to assess adherence thresholds with a particular emphasis on hypertension. Data show that even with the use of electronic monitoring of adherence providing a comprehensive dosing history, it remains extremely difficult to define adherence thresholds in hypertension. This is due to many factors which include not only the pattern of patients’ adherence and their clinical and environmental characteristics, but also the pharmacological properties of drugs and the disease. To determine adherence cut-offs more precisely, specific protocols should be designed to answer the question in various clinical conditions. These protocols should use the most reliable methods to assess adherence providing a detailed dosing history. Datasets should be solid and large enough to be able to analyse adherence data as a continuous variable using new mathematical models including metrics catching the complexity of adherence. The actual development of informatics technologies will provide new solutions to improve our ability to define valid and clinically useful adherence thresholds in various therapeutic areas.